The case of the missing carrot cake - Newman, Robin (Newman, Robin. Wilcox and Griswold mystery., 2015)
When Miss Rabbit's carrot cake goes missing on Ed's farm, Detectives Wilcox and Griswold do what it takes to track down the thieves.